Current floristic and phytogeographic knowledge of Mexican Bromeliaceae - Adolfo Espejo Serna; Ana Rosa López-Ferrari (Revista de Biología Tropical, 1998)
A current floristic and phytogeographic knowledge of native Mexican Bromeliaceae is presented. There are 22 genera of Bromeliaceae recorded from the country that include 326 species. The genus Ursulaea with 2 species is endemic to Mexico, while Hechtia with 48 of its 50 species has its principal center of diversity in the country. Tillandsia (175 spp), Hechtia (48 spp) and Pitcairnia (46 spp) are the genera with the greatest number of species. We present a comparative analysis of Mexican Bromeliaceae with that of other American regions that have recently published accounts for the Family, particularly the Mesomerican area, Venezuela, Ecuador, and the Guianas. Our results led us to the conclusion that all these floras should be considered as distinct. We observe a progressive decrease of the Simpson index value related with the remoteness of the Mexican area. A general analysis of the species numbers of Mexican bromeliad genera shows a distinct preference of the species for coniferous and oak forests, followed by tropical caducifolious forests. There is also significant representation of the family in other vegetation types such as cloud forests and tropical perennifolious forests. Generally Mexican Bromeliaceae species have scarce and sparse populations and in many cases they inhabit cliffs, bluffs and scarps in restricted areas. Concerning the geographic distribution of Mexican genera, 77.27 % are neotropical, 4.54% are South American and the remainder are Mexican and Central American. The generic endemism is very low (4.54 %), even if we extend the country limits to Megamexico sensu Rzedowsi (1991) it reaches only 13.63 %. The family endemism at specific level reaches 63.07 %. There are not available data about a specific analysis of the conservation status of Mexican Bromeliaceae, but we can point out that a great number of taxa are only known from the type collection or at the most from the type locality. This can perhaps be attributed in part to the fact that there is a lack of sufficient collections; however, we suppose that several species are surely endangered. Se presenta el estado del conocimiento florístico-fitogeográfico que se tiene actualmente sobre los representantes silvestres de la familia Bromeliaceae para México. Hasta el momento se tienen registrados a nivel nacional 22 géneros representados por 326 especies. Ursulaea género con 2 especies es endémico al país, en tanto que Hechtia tiene su centro principal de radiación en México, ya que 48 de sus 50 especies se presentan en la República Mexicana, siendo 43 de ellas, (91.5 %), endémicas. Los géneros con mayor número de especies son Tillandsia (175 spp), Hechtia (48 spp) y Pitcairnia (46 spp). Se presenta un análisis comparativo de las Bromeliáceas mexicanas con las de otras regiones de América, con base en tratamientos para la familia recientemente publicados, particularmente para el área mesoamericana, Venezuela, Ecuador y las Guyanas. Los resultados de dicho análisis nos permiten concluir que la flora bromeliológica presente en cada área es distinta y que se observa un decremento en el valor del índice de Simpson en relación con la lejanía de las áreas con respecto a México. Asimismo el análisis general de las especies presentes en los diversos tipos de vegetación, muestra una clara preferencia de las mismas por los bosques de coníferas y de encinos seguidos por los bosques tropicales caducifolios. También es significativa su representación en otros tipos de vegetación como los bosques mesófilos y los bosques tropicales perennifolios. Generalmente las especies de Bromeliáceas mexicanas presentan poblaciones escasas y esparcidas y en muchos casos se las encuentra en riscos y acantilados en áreas muy restringidas. En lo relativo a la distribución geográfica de los géneros mexicanos, el 77.27 % son neotropicales, el 4.54 % son sudamericanos y el porcentaje restantes pertence a taxa mexicanos y centroamericanos. El endemismo genérico es muy bajo (4.54 %) y aún si extendieramos los límites del país a lo que Rzedowski (1991) llama Megaméxico, sólo alcanzaría un 13.63 %. El endemismo de la familia a nivel específico alcanza 63.07 %.